PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KARYAWAN PT. TVS COMPANY - Siwi Nur Indriyani (Jurnal Ekonomi dan Industri, 2023)
The purpose of this study is to analyze the influence of leadership and motivation on employee productivity of PT. TVS Company. This type of research is included in the category of causal associative quantitative research. The source of research data is primary data using a questionnaire with a Likert. The sampling technique used is a saturated sample. The research was conducted of PT. TVS Company employees. The analytical technique used in this study is multiple linear regression analysis. The results of the analysis show that leadership and motivation either part.